Electrically and Optically Controllable p–n Junction Memtransistor Based on an Al2O3 Encapsulated 2D Te/ReS2 van der Waals Heterostructure (Small Methods 12/2021). Issue 12 (13th December 2021) - Nguyen, Duc Anh; Jo, Yongcheol; Tran, Thi Uyen; Jeong, Mun Seok; Kim, Hyungsang; Im, Hyunsik
Abstract : Inside Front Cover In article number 2101303, Im and co‐workers have demonstrated an electrically and optically controllable p‐n junction memtransistor using an Al2 O3 encapsulated 2D Te/ReS2 van der Waals heterostructure. The hybrid memtransistor shows a high switching ratio at a low operating voltage, high cycling endurance, and long retention time. It successfully functions as a multiterminal non‐volatile memory, multivalued logic gate, and synaptic activities by combining electrical and optical inputs.